Penerapan Work Life Balance Terhadap Produktivitas Karyawan Pada Umkm D’sruput Lubuk Begalung Padang - Elsa Vitaloka; Randi Kurniawan; Sofiatun Nikmah; Yudistira Pratama; Vivi Nila Sari (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of work life balance and its effect on employee productivity at D’sruput UMKM, Lubuk Begalung, Padang. The topic was chosen due to the importance of balancing work and personal life in improving employee performance, especially in small and medium enterprises with limited human resources. This research uses a quantitative approach with data collected through questionnaires distributed to employees. The data were analyzed using descriptive statistical analysis and simple regression analysis to determine the relationship between work life balance and employee productivity. The results indicate that work life balance has a positive and significant effect on employee productivity. Employees who are able to balance their work responsibilities and personal lives tend to show higher levels of productivity. These findings highlight the importance for UMKM to implement work life balance practices as a strategy to enhance employee productivity and organizational performance.